Analysis Effect of Environment Attitude, Health Consciousness and Knowledge in Developing Product Perception and Intention to Buy (A Study on Organic Food Product) - Widyasari, Widyasari; Haryanto, Jony Oktavian (UI Scholars Hub, 2021)
This research intends to study the factors that can affect the product perception and consumer intention in buying organic product.The study is necessary in that it explores at least some of the factors that can affect the product perception and consumer intention in buying organic product. The research results indicated that there was a positive influence of health consciousness towards environment attitude, consumer’s organic product knowledge towards organic product perception, environment attitude and consumer’s organic knowledge towards intention to buy organic product. But, there was a negative influence between environment attitude, health consciousness towards consumer’s organic product perception, and consumer’s organic product towards intention to buy organic product.